Numerical analysis of quadcopter in different weather conditions of regions in India. (2021) - Kumar, Rajiv; Rohit,; Kumar, Gaurav; Zunaid, M.; Ansari, N.A.
Abstract: For photography, remote sensing, aerial surveillance disaster relief and motion picture filmmaking quadcopters are very useful today, and it is essential to find out its limits, so that we can predict in which atmospheric conditions, it works with perfection. And another important factor for quad copter is to know about its effect in order to run smoothly. To overcome these problems, A 3D model of the drone is created on SolidWorks and CFD is performed on Ansys. This simulation results help researchers to see the after effects of different flight condition.